Terapi Radikal pada Penderita Kanker Prostat: Tindak Lanjut Jangka Panjang dan Faktor Prediksi Survival - RAINY UMBAS; CHAIDIR A MOCHTAR; RIZAL A HAMID (Indonesian Journal of Cancer, 2010)
Radical treatment in the form of radical prostatectomy (PR) or external beam radiotherapy (EBRT) considered as gold standard in the management of localized and in some selected cases of locally advanced prostate cancer patients. Aim of this study is to know the treatment results of RP and EBRT in prostate cancer patients with T1-3 at Cipto Mangunkusumo Hospital and Dharmais Cancer Hospital, Jakarta. Analysis to the prediction factors in those two treatment modalities was also done. There were 110 patients among 610 prostate cancer patients in those two hospitals between January 1995 and December 2007 who received radical treatment. Radical prostatectomy was done to 43 patients with median age of 63 years (range: 50-74 years), and the other 67 patients with median age of 70 years (range: 50-82 years) were treated by EBRT. Median survival was 101 months and 85 months for patients treated with RP and EBRT respectively while 5-year survival rate was 68.4% and 69.2% for those respective groups. There was no clinical parameter in the group of patients who underwent PR which significantly correlated with survival. In the EBRT group, low grade tumor was significantly correlated with better survival. In conclussion, less than 20% of prostate cancer patients in those two hospitals underwent radical treatment in form of PR or EBRT. Median survival for patients treated with PR was better than those who received EBRT. Tumor grade was the only survival predictor factor in the EBRT group.